The effect of basic motor abilities on the success in football game of football players aged 13 to 15 year-old - Talovic, M.; Ralo, I.; Jeleskovic, E.; Alic, H. (Homosporticus, 2010)
The aim of this research was to determine the influence of basic motor skills on the success in the game of football players aged 13-15 years. A large number of researchers dealt with this problem and proved a lot in this area, but what might be interesting in this study is the sample of respondents with their characteristics and age can always offer new and interesting facts. Age, which produces large changes in the body also, can cause a variety of phenomena. The sample of respondents in this study were youth football players, whose age was 14, 12 ± 0.93 years. All of them were members of youth school FC Krajina,Cazin and members of cadets selection, from which a sample of 120 respondents have been taken. The respondents were taken from the football school FC Krajina - Cazin, FC Jedinstvo - Bihac and FC Krajisnik - Velika Kladusa. The sample of variables in this study is the variables of basic motor skills as predictors (17) and the variables of success in the football game as the criterion (8). Based on statistical data - regression analysis determined the impact of individual motor variables. It turned out that the system of predictor variables, which consisted of basic motor abilities had a statistically significant association (p> 0.05) with the measured indicators of success in the game, so you may notice that the largest and statistically significant impact on the criterion variable has MKLSNL - slalom with two balls, with a significance level of .01. A variable that is allocated determines the latent dimension of coordination. In addition, we can certainly say that all movements and everything that happens during the game is determined by coordination skills, whether it is a game in attack or defense.